Information Needs of Indonesian Infertile Patients About Cross-Border Reproductive Care - Rumyeni Rumyeni; Susanne Dida; Purwanti Hadisiwi; Yanti Setianti (UIR Press, 2021)
Infertile patients need to prepare variety of information before decided to perform reproductive care procedures in foreign country. Sufficient information will help the reproductive care run smoothly. The purpose of this study is to determine the source of information, the necessary information, and the barriers to fulfill the necessary information of Indonesian infertile patients undergoing IVF programs in Malaysia. This study used qualitative method by conducting in-depth interviews with 11 infertile patients who had IVF experience in Malaysia. Results showed that infertile patients obtained information about the IVF program in Malaysia through four sources of information, namely: 1) personal sources such as friends and family; 2) online media which includes the google search engine, blogs and youtube; 3) medical professionals, whether doctors, nurses or other medical personnel; and 4) seminars held by hospital management. Patients information needs include specific information about IVF, medical system information, cost information, IVF legal information, and easiness information in the destination country. Language was found as an obstacle in fulfilled information needs. In conclusion, this study provides new knowledge about various sources of information used by infertile patients in fulfil their information needs about cross-border reproductive care procedures, with language as one of the obstacles.